Description of a new fossil Statira Lepeletier et Audinet-Serville, 1828 (Coleoptera: Tenebrionidae: Lagriinae) from Baltic amber of the Sambian Peninsula - Telnov, Dmitry; Bukejs, Andris; Merkl, Ottó (Zootaxa, 2019)
Statira baltica sp. nov. is described from Eocene Baltic amber found in the Baltic Sea coast, Yantarny settlement, Kaliningrad Region, Russia. This is the second described fossil member of the genus Statira Lepeletier et Audinet-Serville, 1828 and the tribe Lagriini Latreille, 1825, and the first from outside the New World.